Halogen-free high Tg high CTI flame retardant resin composition and preparation method thereof and laminate

By adding nanocomposite materials of carbon nanotubes and cellulose nanocrystals to the resin of the copper-clad foil laminate, and combining specific epoxy resin monomers and block copolymers, the problems of flammable, low CTI and high dielectric loss of existing laminates are solved, and the comprehensive performance of halogen-free, high Tg, high CTI and low dielectric loss is achieved.

CN119752110APending Publication Date: 2025-04-04CHONGQING DEKAI IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411613195.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing copper clad laminate has problems such as flammability, low CTI, high dielectric loss and insufficient glass transition temperature, and it is difficult to meet the performance requirements of halogen-free, high Tg, high CTI and low dielectric loss at the same time.

Method used

By adding carbon nanotubes and cellulose nanocrystals to the vinyl acetate grafted ethylene propylene dimer rubber graft copolymer, EPR-g-Vac/CNTs/NCC nanocomposites are formed, and mixed with barium sulfate and aluminum hydroxide to form fillers. Then, eugenol-based cyclotriphosphazene epoxy resin monomer, glycidyl ether type tetrafunctional epoxy resin and hydrogenated styrene-butadiene-styrene block copolymer are added to the resin to improve the crosslinking degree and flame retardant properties of the resin.

Benefits of technology

A laminate with halogen-free, high Tg, high CTI, low dielectric loss and high flame retardant properties is achieved, and the hot press curing parameters are optimized to improve the curing effect of the resin.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a halogen-free high Tg high CTI flame retardant resin composition and a preparation method and a laminate, which belongs to the technical field of electronic materials. First, a filler is prepared, including preparing an EPR-g-Vac / CNTs / NCC nanocomposite material, mixing the EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide in a weight ratio of 8 to 10: 1.5 to 3: 1.3 to 1.8 to obtain a filler, and then dispersing the filler; then preparing a composite resin, and putting the resin into a groove; adding a curing agent for a curing reaction to obtain a resin composition, and measuring S / G in the range of 280 to 295S is qualified. The laminate prepared by the present invention has the advantages of high glass transition temperature Tg, high flame retardant performance, high tracking index CTI, high thermal stratification time T288, and low dielectric loss factor Df.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic materials, and in particular to a halogen-free high-Tg and high-CTI flame-retardant resin composition, a preparation method thereof, and a laminate. Background Art

[0002] With the development of the electrical industry, copper clad laminates have been widely used.

[0003] Epoxy resin is the base resin of copper-clad laminates. Its structure contains epoxy groups at both ends, and the main chain contains more ether bonds, secondary hydroxyl groups, benzene rings, methine, and isopropyl groups. These structural units give bisphenol A epoxy resin many good properties. However, the copper-clad laminate is flammable. In order to improve its flame retardant properties, it is necessary to use flame retardants for flame retardant modification. Halogen (Br and other elements) flame retardants have good effects but can cause environmental damage. At the same time, due to the low CTI (tracking index) of the copper-clad laminate, it is generally difficult to reach more than 400V, which causes the surface of the copper-clad laminate to easily generate sparks, reduce insulation, and even cause breakdown short circuit or open circuit.

[0004] In high-frequency circuits, the dielectric loss (Df) of copper-clad laminates greatly affects the transmission loss of electrical signals. The transmission loss is proportional to Df, so it is necessary to reduce the Df of copper-clad laminates. At the same time, due to the high operating temperature, the glass transition temperature (Tg) of the material is required to be high.

[0005] CN110561855B discloses a halogen-free medium Tg high CTI flame-retardant epoxy glass fiber cloth-based laminate and a preparation method thereof. The copper clad laminate prepared therefrom has medium Tg (155°C), high CTI (650V), and high flame retardancy (V-0) properties, but its Tg still does not meet the high Tg requirements, and its Df performance is unknown.

[0006] Therefore, it is of high technical and economic value to develop resin composite materials that have the requirements of halogen-free, low Df, high Tg, high CTI and high flame retardant properties.

[0007] Based on this, the present invention designs a halogen-free high Tg and high CTI flame retardant resin composition and a preparation method thereof and a laminate to solve the above problems. Summary of the invention

[0008] In view of the above-mentioned shortcomings of the prior art, the present invention provides a halogen-free high-Tg and high-CTI flame retardant resin composition, a preparation method thereof, and a laminate.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0011] 1. Preparation of filler:

[0012] 1.1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 1-3 parts of carbon nanotubes and 6-11 parts of cellulose nanocrystals are added to 10-12 parts of vinyl acetate grafted ethylene propylene rubber grafted copolymer to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite;

[0013] 1.2. Evenly mix the EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide in a weight ratio of 8-10:1.5-3:1.3-1.8 to obtain a filler;

[0014] 2. Dispersion of fillers: first, add 60-70 parts of propylene glycol methyl ether into the reaction kettle, start high-speed stirring, add 12-17 parts of poly(ethylene methyl phosphonate) and 85-95 parts of fillers, and stir evenly;

[0015] 3. Prepare the composite resin and then put it into the tank: take 200-250 parts of solvent, 35-48 parts of bisphenol A epoxy resin, 3-7 parts of eugenol-based cyclotriphosphazene epoxy resin monomer, 22-28 parts of glycidyl ether type tetrafunctional epoxy resin, 10-13 parts of hydrogenated styrene-butadiene-styrene block copolymer, stir and react at 74-80°C for 2-3h to obtain a composite resin, and put the composite resin into a reaction kettle;

[0016] 4. Adding curing agent: adding 11 to 13 parts of curing agent into the reaction kettle, allowing it to fully cure with the composite resin, and continuously stirring for 4 to 5 hours to obtain a resin composition;

[0017] 5. Stop the machine to measure S / G: Take an appropriate amount of resin composition and test the S / G of the resin composition. The S / G is qualified when it is within the range of 280~295S.

[0018] Furthermore, in step 2, the filler is added while stirring, and stirring is continued for more than 2 hours after the addition is completed, and the stirring speed is higher than 1300r / min.

[0019] Furthermore, in step three, the solvent is butanone.

[0020] Furthermore, in step 4, the curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde, and benzoxazine resin in a weight ratio of 11-13:8-11:3-9.

[0021] Furthermore, in step 5, if the S / G of the resin composition is greater than 295S, 0.5-1% by weight of the resin composition of 2-methylimidazole is added gradually, mixed evenly, and then the S / G is measured until the S / G reaches a range of 280-295S.

[0022] Furthermore, in step three, the mass ratio of the total mass of the eugenol-based cyclotriphosphazene epoxy resin monomer, the glycidyl ether-type tetrafunctional epoxy resin and the hydrogenated styrene-butadiene-styrene block copolymer to the bisphenol A-type epoxy resin is 1:1.

[0023] In order to better achieve the purpose of the present invention, the present invention also provides a halogen-free high Tg and high CTI flame retardant resin composition.

[0024] In order to better achieve the purpose of the present invention, the present invention also provides a use of a halogen-free high Tg and high CTI flame retardant resin composition in the preparation of a laminate.

[0025] In order to better achieve the purpose of the present invention, the present invention also provides a laminated board, using the halogen-free high Tg high CTI flame retardant resin composition, the preparation method comprises the following steps:

[0026] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0027] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0028] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0029] The gelation temperature is 122-131°C, the pressure is 28-30 MPa, and the time is 1-1.2 hours;

[0030] Curing temperature 158~163℃, pressure 48~51Mpa, time 1~1.1h;

[0031] Post-curing temperature is 178-184°C, pressure is 30-33Mpa, and time is 0.8-1h.

[0032] Furthermore, the method further comprises step (4) cutting: cutting off the edge material of the laminate substrate to obtain the laminate, and then packing after inspection.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The invention adds carbon nanotubes (CNTs) and cellulose nanocrystals (NCC) into a vinyl acetate grafted ethylene propylene rubber grafted copolymer (EPR-g-VAc), and the EPR-g-VAc covers the CNTs and NCC to form a core-shell structure, thereby obtaining an EPR-g-Vac / CNTs / NCC nanocomposite material. The carbon nanotubes and cellulose nanocrystals have excellent high temperature resistance and thermal conductivity. After forming a core-shell structure with the vinyl acetate grafted ethylene propylene rubber grafted copolymer, the composite resin can be effectively reinforced, which is beneficial to improving the glass transition temperature Tg, the tracking index CTI, and the thermal delamination time T288 of the laminated board, and reducing the dielectric loss factor Df of the laminated board. The addition of the eugenol-based cyclotriphosphazene epoxy resin monomer is beneficial to improving the flame retardant performance, and the addition of the glycidyl ether-type tetrafunctional epoxy resin is beneficial to increasing the molecular chain The cross-linking degree of hydrogenated styrene-butadiene-styrene block copolymer is high in saturation degree of the main chain, and the chain segments are highly entangled, which is beneficial to further improve the cross-linking effect of the composite resin system. When the content of bisphenol A epoxy resin is increased or decreased, the glass transition temperature Tg, flame retardancy, tracking index CTI, thermal delamination time T288, and dielectric loss factor Df of the laminate are greatly affected. The optimal ratio of the composite resin system is as follows: the total mass ratio of eugenol-based cyclotriphosphazene epoxy resin monomer, glycidyl ether-type tetrafunctional epoxy resin and hydrogenated styrene-butadiene-styrene block copolymer to bisphenol A epoxy resin is 1:1. The laminate prepared under this ratio has the advantages of high glass transition temperature Tg, high flame retardancy, high tracking index CTI, high thermal delamination time T288, and low dielectric loss factor Df.

[0035] In addition, when the halogen-free high Tg and high CTI flame retardant resin composition of the present invention is used to prepare a laminate, its hot pressing curing parameters are optimized (reduced): gel temperature 122-131°C, pressure 28-30 MPa, time 1-1.2 h; curing temperature 158-163°C, pressure 48-51 MPa, time 1-1.1 h; post-curing temperature 178-184°C, pressure 30-33 MPa, time 0.8-1 h. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0039] 1. Preparation of filler:

[0040] 1.1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 1 part of carbon nanotubes (CNTs) and 6 parts of cellulose nanocrystals (NCC) were added to 10 parts of vinyl acetate grafted ethylene propylene rubber graft copolymer (EPR-g-VAc), and EPR-g-VAc coated CNTs and NCC to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite;

[0041] 1.2. The EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide are uniformly mixed in a weight ratio of 8:1.5:1.3 to obtain a filler;

[0042] 2. Filler dispersion: first, add 60 parts of propylene glycol methyl ether (PM) into the reactor, start high-speed stirring, add 12 parts of poly(ethylene glycol methyl phosphonate) and 85 parts of filler. The filler must be added while stirring. After the addition is completed, continue stirring for 2.2 hours, and the stirring speed is 1500r / min;

[0043] 3. Preparation of composite resin and resin tank: 200 parts of solvent, 35 parts of bisphenol A epoxy resin, 3 parts of eugenol-based cyclotriphosphazene epoxy resin monomer (EQDEP), 22 parts of glycidyl ether tetrafunctional epoxy resin, 10 parts of hydrogenated styrene-butadiene-styrene block copolymer were taken, and stirred at 74°C for 2 hours to obtain a composite resin, and the composite resin was poured into a reaction kettle;

[0044] The solvent is butanone;

[0045] 4. Adding curing agent: adding 11 parts of curing agent into the reaction kettle, allowing it to fully cure with the above composite resin, and continuously stirring for 4 hours to obtain a resin composition;

[0046] The curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde and benzoxazine resin in a weight ratio of 11:8:3;

[0047] 5. Stop the machine to measure S / G: Draw an appropriate amount of resin composition and test the S / G (curing time) of the resin composition. If the S / G is within the range of 280 to 295S, it is qualified.

[0048] The method of preparing a laminate using a halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0049] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0050] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0051] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0052] Gel temperature 122°C, pressure 30 MPa, time 1 h;

[0053] Curing temperature 158℃, pressure 51Mpa, time 1h;

[0054] Post-curing temperature: 178°C, pressure: 33Mpa, time: 0.8h;

[0055] High temperature and high pressure are used to melt the resin, completely expel the gas, and completely solidify the resin, thereby completing a firm bond between the prepreg layers and between the prepreg and the copper foil.

[0056] (4) Cutting: Cut off the edge of the laminate substrate to obtain the laminate, and then pack it after inspection.

[0057] Example 2

[0058] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0059] 1. Preparation of filler:

[0060] 1.1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 3 parts of carbon nanotubes (CNTs) and 11 parts of cellulose nanocrystals (NCC) were added to 12 parts of vinyl acetate grafted ethylene propylene rubber graft copolymer (EPR-g-VAc), and EPR-g-VAc coated CNTs and NCC to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite;

[0061] 1.2. The EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide are uniformly mixed in a weight ratio of 10:3:1.8 to obtain a filler;

[0062] 2. Filler dispersion: first, add 70 parts of propylene glycol methyl ether (PM) into the reactor, start high-speed stirring, add 17 parts of poly(ethylene methyl phosphonate) and 95 parts of filler. The filler must be added while stirring. After the addition is completed, continue stirring for 2.5 hours at a stirring speed of 1400r / min.

[0063] 3. Preparation of composite resin and resin tank: 250 parts of solvent, 48 parts of bisphenol A epoxy resin, 7 parts of eugenol-based cyclotriphosphazene epoxy resin monomer (EQDEP), 28 parts of glycidyl ether tetrafunctional epoxy resin, 13 parts of hydrogenated styrene-butadiene-styrene block copolymer were taken, and stirred at 80°C for 3 hours to obtain a composite resin, and the composite resin was poured into a reaction kettle;

[0064] The solvent is butanone;

[0065] 4. Adding curing agent: adding 13 parts of curing agent into the reaction kettle, allowing it to fully cure with the above composite resin, and continuously stirring for 5 hours to obtain a resin composition;

[0066] The curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde and benzoxazine resin in a weight ratio of 13:11:9;

[0067] 5. Stop the machine to measure S / G: Draw an appropriate amount of resin composition and test the S / G (curing time) of the resin composition. If the S / G is within the range of 280 to 295S, it is qualified.

[0068] The method of preparing a laminate using a halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0069] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0070] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0071] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0072] Gel temperature 128°C, pressure 29 MPa, time 1 h;

[0073] Curing temperature 163°C, pressure 48Mpa, time 1.1h;

[0074] Post-curing temperature 180°C, pressure 31Mpa, time 0.9h;

[0075] High temperature and high pressure are used to melt the resin, completely expel the gas, and completely solidify the resin, thereby completing a firm bond between the prepreg layers and between the prepreg and the copper foil.

[0076] (4) Cutting: Cut off the edge of the laminate substrate to obtain the laminate, and then pack it after inspection.

[0077] Example 3

[0078] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0079] 1. Preparation of filler:

[0080] 1.1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 2.4 parts of carbon nanotubes (CNTs) and 10 parts of cellulose nanocrystals (NCC) were added to 11 parts of vinyl acetate grafted ethylene propylene rubber graft copolymer (EPR-g-VAc), and EPR-g-VAc coated CNTs and NCC to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite;

[0081] 1.2. The EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide are uniformly mixed in a weight ratio of 9:2.3:1.5 to obtain a filler;

[0082] 2. Filler dispersion: first, add 65 parts of propylene glycol methyl ether (PM) into the reactor, start high-speed stirring, add 15 parts of poly(ethylene methyl phosphonate) and 90 parts of filler. The filler must be added while stirring. After the addition is completed, continue stirring for 3 hours, and the stirring speed is higher than 1600r / min;

[0083] 3. Preparation of composite resin and resin tank: 230 parts of solvent, 40 parts of bisphenol A epoxy resin, 5 parts of eugenol-based cyclotriphosphazene epoxy resin monomer (EQDEP), 24 parts of glycidyl ether tetrafunctional epoxy resin, 11 parts of hydrogenated styrene-butadiene-styrene block copolymer were taken, and stirred at 78°C for 2.3 hours to obtain a composite resin, and the composite resin was poured into a reaction kettle;

[0084] The solvent is butanone;

[0085] 4. Adding curing agent: adding 12 parts of curing agent into the reaction kettle, allowing it to fully cure with the composite resin, and continuously stirring for 4.6 hours to obtain a resin composition;

[0086] The curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde and benzoxazine resin in a weight ratio of 12:10:5;

[0087] 5. Stop the machine to measure S / G: Draw an appropriate amount of resin composition and test the S / G (curing time) of the resin composition. If the S / G is within the range of 280 to 295S, it is qualified.

[0088] The method of preparing a laminate using a halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0089] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0090] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0091] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0092] Gel temperature 131°C, pressure 28 MPa, time 1.2 h;

[0093] Curing temperature 159°C, pressure 50Mpa, time 1h;

[0094] Post-curing temperature: 184°C, pressure: 30 MPa, time: 1 h;

[0095] High temperature and high pressure are used to melt the resin, completely expel the gas, and completely solidify the resin, thereby completing a firm bond between the prepreg layers and between the prepreg and the copper foil.

[0096] (4) Cutting: Cut off the edge of the laminate substrate to obtain the laminate, and then pack it after inspection.

[0097] Comparative Example 1

[0098] Different from Example 3, no EPR-g-Vac / CNTs / NCC nanocomposite material is used in the raw materials.

[0099] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0100] 1. Prepare filler: mix barium sulfate and aluminum hydroxide in a weight ratio of 2.3:1.5 to obtain filler;

[0101] 2. Filler dispersion: first, add 65 parts of propylene glycol methyl ether (PM) into the reactor, start high-speed stirring, add 15 parts of poly(ethylene methyl phosphonate) and 90 parts of filler. The filler must be added while stirring. After the addition is completed, continue stirring for 3 hours, and the stirring speed is higher than 1600r / min;

[0102] 3. Preparation of composite resin and resin tank: 230 parts of solvent, 40 parts of bisphenol A epoxy resin, 5 parts of eugenol-based cyclotriphosphazene epoxy resin monomer (EQDEP), 24 parts of glycidyl ether tetrafunctional epoxy resin, 11 parts of hydrogenated styrene-butadiene-styrene block copolymer were taken, and stirred at 78°C for 2.3 hours to obtain a composite resin, and the composite resin was poured into a reaction kettle;

[0103] The solvent is butanone;

[0104] 4. Adding curing agent: adding 12 parts of curing agent into the reaction kettle, allowing it to fully cure with the composite resin, and continuously stirring for 4.6 hours to obtain a resin composition;

[0105] The curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde and benzoxazine resin in a weight ratio of 12:10:5;

[0106] 5. Stop the machine to measure S / G: Draw an appropriate amount of resin composition and test the S / G (curing time) of the resin composition. If the S / G is within the range of 280 to 295S, it is qualified.

[0107] The method of preparing a laminate using a halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0108] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0109] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0110] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0111] Gel temperature 131°C, pressure 28 MPa, time 1.2 h;

[0112] Curing temperature 159°C, pressure 50Mpa, time 1h;

[0113] Post-curing temperature: 184°C, pressure: 30 MPa, time: 1 h;

[0114] High temperature and high pressure are used to melt the resin, completely expel the gas, and completely solidify the resin, thereby completing a firm bond between the prepreg layers and between the prepreg and the copper foil.

[0115] (4) Cutting: Cut off the edge of the laminate substrate to obtain the laminate, and then pack it after inspection.

[0116] Comparative Example 2

[0117] Different from Example 3, the mass ratio of the total mass of the eugenol-based cyclotriphosphazene epoxy resin monomer, the glycidyl ether-type tetrafunctional epoxy resin and the hydrogenated styrene-butadiene-styrene block copolymer to the bisphenol A-type epoxy resin is 2:1.

[0118] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0119] 1. Preparation of filler:

[0120] 1.1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 2.4 parts of carbon nanotubes (CNTs) and 10 parts of cellulose nanocrystals (NCC) were added to 11 parts of vinyl acetate grafted ethylene propylene rubber graft copolymer (EPR-g-VAc), and EPR-g-VAc coated CNTs and NCC to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite;

[0121] 1.2. The EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide are uniformly mixed in a weight ratio of 9:2.3:1.5 to obtain a filler;

[0122] 2. Filler dispersion: first, add 65 parts of propylene glycol methyl ether (PM) into the reactor, start high-speed stirring, add 15 parts of poly(ethylene methyl phosphonate) and 90 parts of filler. The filler must be added while stirring. After the addition is completed, continue stirring for 3 hours, and the stirring speed is higher than 1600r / min;

[0123] 3. Preparation of composite resin and resin tank: 230 parts of solvent, 20 parts of bisphenol A epoxy resin, 5 parts of eugenol-based cyclotriphosphazene epoxy resin monomer (EQDEP), 24 parts of glycidyl ether tetrafunctional epoxy resin, 11 parts of hydrogenated styrene-butadiene-styrene block copolymer were taken, and stirred at 78°C for 2.3 hours to obtain a composite resin, and the composite resin was poured into a reaction kettle;

[0124] The solvent is butanone;

[0125] 4. Adding curing agent: adding 12 parts of curing agent into the reaction kettle, allowing it to fully cure with the composite resin, and continuously stirring for 4.6 hours to obtain a resin composition;

[0126] The curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde and benzoxazine resin in a weight ratio of 12:10:5;

[0127] 5. Stop the machine to measure S / G: Draw an appropriate amount of resin composition and test the S / G (curing time) of the resin composition. If the S / G is within the range of 280 to 295S, it is qualified.

[0128] The method of preparing a laminate using a halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0129] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0130] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0131] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0132] Gel temperature 131°C, pressure 28 MPa, time 1.2 h;

[0133] Curing temperature 159°C, pressure 50Mpa, time 1h;

[0134] Post-curing temperature: 184°C, pressure: 30 MPa, time: 1 h;

[0135] High temperature and high pressure are used to melt the resin, completely expel the gas, and completely solidify the resin, thereby completing a firm bond between the prepreg layers and between the prepreg and the copper foil.

[0136] (4) Cutting: Cut off the edge of the laminate substrate to obtain the laminate, and then pack it after inspection.

[0137] Comparative Example 3

[0138] Different from Example 3, the mass ratio of the total mass of the eugenol-based cyclotriphosphazene epoxy resin monomer, the glycidyl ether tetrafunctional epoxy resin and the hydrogenated styrene-butadiene-styrene block copolymer to the bisphenol A epoxy resin is 1:2.

[0139] The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0140] 1. Preparation of filler:

[0141] 1.1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 2.4 parts of carbon nanotubes (CNTs) and 10 parts of cellulose nanocrystals (NCC) were added to 11 parts of vinyl acetate grafted ethylene propylene rubber graft copolymer (EPR-g-VAc), and EPR-g-VAc coated CNTs and NCC to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite;

[0142] 1.2. The EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide are uniformly mixed in a weight ratio of 9:2.3:1.5 to obtain a filler;

[0143] 2. Filler dispersion: first, add 65 parts of propylene glycol methyl ether (PM) into the reactor, start high-speed stirring, add 15 parts of poly(ethylene methyl phosphonate) and 90 parts of filler. The filler must be added while stirring. After the addition is completed, continue stirring for 3 hours, and the stirring speed is higher than 1600r / min;

[0144] 3. Preparation of composite resin and resin tank: 230 parts of solvent, 80 parts of bisphenol A epoxy resin, 5 parts of eugenol-based cyclotriphosphazene epoxy resin monomer (EQDEP), 24 parts of glycidyl ether tetrafunctional epoxy resin, 11 parts of hydrogenated styrene-butadiene-styrene block copolymer were taken, and stirred at 78°C for 2.3 hours to obtain a composite resin, and the composite resin was poured into a reaction kettle;

[0145] The solvent is butanone;

[0146] 4. Adding curing agent: adding 12 parts of curing agent into the reaction kettle, allowing it to fully cure with the composite resin, and continuously stirring for 4.6 hours to obtain a resin composition;

[0147] The curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde and benzoxazine resin in a weight ratio of 12:10:5;

[0148] 5. Stop the machine to measure S / G: Draw an appropriate amount of resin composition and test the S / G (curing time) of the resin composition. If the S / G is within the range of 280 to 295S, it is qualified.

[0149] The method of preparing a laminate using a halogen-free high Tg and high CTI flame retardant resin composition comprises the following steps:

[0150] (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg;

[0151] (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly;

[0152] (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are:

[0153] Gel temperature 131°C, pressure 28 MPa, time 1.2 h;

[0154] Curing temperature 159°C, pressure 50Mpa, time 1h;

[0155] Post-curing temperature: 184°C, pressure: 30 MPa, time: 1 h;

[0156] High temperature and high pressure are used to melt the resin, completely expel the gas, and completely solidify the resin, thereby completing a firm bond between the prepreg layers and between the prepreg and the copper foil.

[0157] (4) Cutting: Cut off the edge of the laminate substrate to obtain the laminate, and then pack it after inspection.

[0158] Experimental example

[0159] The performance of the laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:

[0160] Table 1 Performance test comparison of laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0161] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Glass transition temperature Tg (℃, DSC) 315 297 349 267 237 205 Flame retardant UL94 V-0 V-0 V-0 V-0 V-0 V-1 Dielectric loss factor Df(10GHz) 0.006 0.005 0.006 0.014 0.012 0.009 Tracking Index CTI(V) 580 597 579 509 369 297 Thermal stratification time T288, min >70 >70 >70 40 >70 60 Water absorption % 0.16 0.16 0.15 0.16 0.15 0.16 Peel strength N / mm 1.70 1.75 1.67 1.61 1.57 1.66

[0162] The invention adds carbon nanotubes (CNTs) and cellulose nanocrystals (NCC) into vinyl acetate grafted ethylene propylene rubber grafted copolymer (EPR-g-VAc), and the EPR-g-VAc covers the CNTs and NCC to form a core-shell structure, thereby obtaining an EPR-g-Vac / CNTs / NCC nanocomposite material. The carbon nanotubes and cellulose nanocrystals have excellent high temperature resistance and thermal conductivity. After forming a core-shell structure with the vinyl acetate grafted ethylene propylene rubber grafted copolymer, the core-shell structure is conducive to crosslinking with the composite resin, can effectively strengthen the composite resin, and is conducive to improving the glass transition temperature Tg, the tracking index CTI, and the thermal stratification time T288 of the laminated board, and reducing the dielectric loss factor Df of the laminated board. The addition of the eugenol-based cyclotriphosphazene epoxy resin monomer is conducive to improving the flame retardant performance, the addition of the glycidyl ether type tetrafunctional epoxy resin is conducive to increasing the crosslinking degree of the molecular chain, and the main structure of the hydrogenated styrene-butadiene-styrene block copolymer is conducive to improving the flame retardant performance. The high chain saturation and high entanglement of chain segments are conducive to further improving the crosslinking effect of the composite resin system. When the content of bisphenol A epoxy resin is increased or decreased, the glass transition temperature Tg, flame retardancy, tracking index CTI, thermal delamination time T288, and dielectric loss factor Df of the laminate are greatly affected. This may be due to the excessive degree of entanglement and crosslinking between the core-shell structure and the glycidyl ether tetrafunctional epoxy resin, hydrogenated styrene-butadiene-styrene block copolymer, etc. The optimum ratio of the composite resin system is as follows: the total mass ratio of eugenol-based cyclotriphosphazene epoxy resin monomer, glycidyl ether-type tetrafunctional epoxy resin and hydrogenated styrene-butadiene-styrene block copolymer to bisphenol A-type epoxy resin is 1:1. The laminate prepared under this ratio has the advantages of high glass transition temperature Tg, high flame retardant performance, high tracking index CTI, high thermal delamination time T288 and low dielectric loss factor Df.

[0163] In addition, when the halogen-free high Tg and high CTI flame retardant resin composition of the present invention is used to prepare a laminate, its hot pressing curing parameters are optimized (reduced): gel temperature 122-131°C, pressure 28-30 MPa, time 1-1.2 h; curing temperature 158-163°C, pressure 48-51 MPa, time 1-1.1 h; post-curing temperature 178-184°C, pressure 30-33 MPa, time 0.8-1 h.

[0164] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a halogen-free high Tg high CTI flame retardant resin composition, characterized in that it comprises the following steps:

1. Preparation of filler: 1.

1. Preparation of EPR-g-Vac / CNTs / NCC nanocomposite: 1-3 parts of carbon nanotubes and 6-11 parts of cellulose nanocrystals are added to 10-12 parts of vinyl acetate grafted ethylene propylene rubber grafted copolymer to form a core-shell structure to obtain EPR-g-Vac / CNTs / NCC nanocomposite; 1.

2. Evenly mix the EPR-g-Vac / CNTs / NCC nanocomposite material, barium sulfate and aluminum hydroxide in a weight ratio of 8-10:1.5-3:1.3-1.8 to obtain a filler; 2. Dispersion of fillers: first, add 60-70 parts of propylene glycol methyl ether into the reaction kettle, start high-speed stirring, add 12-17 parts of poly(ethylene methyl phosphonate) and 85-95 parts of fillers, and stir evenly; 3. Prepare the composite resin and then put it into the tank: take 200-250 parts of solvent, 35-48 parts of bisphenol A epoxy resin, 3-7 parts of eugenol-based cyclotriphosphazene epoxy resin monomer, 22-28 parts of glycidyl ether type tetrafunctional epoxy resin, 10-13 parts of hydrogenated styrene-butadiene-styrene block copolymer, stir and react at 74-80°C for 2-3h to obtain a composite resin, and put the composite resin into a reaction kettle; 4. Adding curing agent: adding 11 to 13 parts of curing agent into the reaction kettle, allowing it to fully cure with the composite resin, and continuously stirring for 4 to 5 hours to obtain a resin composition; 5. Stop the machine to measure S / G: Take an appropriate amount of resin composition and test the S / G of the resin composition. The S / G is qualified when it is within the range of 280~295S.

2. The method for preparing the halogen-free high Tg high CTI flame retardant resin composition according to claim 1, characterized in that: In step 2, the filler is added while stirring, and stirring is continued for more than 2 hours after the addition is completed, and the stirring speed is higher than 1300r / min.

3. The method for preparing the halogen-free high Tg high CTI flame retardant resin composition according to claim 2, characterized in that: In step 3, the solvent is butanone.

4. The method for preparing the halogen-free high Tg and high CTI flame retardant resin composition according to claim 3, characterized in that: In step 4, the curing agent is prepared by mixing linear phenolic formaldehyde, phosphorus-containing phenolic formaldehyde, and benzoxazine resin in a weight ratio of 11-13:8-11:3-9.

5. The method for preparing the halogen-free high Tg and high CTI flame retardant resin composition according to claim 4, characterized in that: In step 5, if the S / G of the resin composition is greater than 295S, 0.5-1% by weight of the resin composition of 2-methylimidazole is added gradually, and after mixing evenly, the S / G is measured until the S / G reaches the range of 280-295S.

6. The method for preparing the halogen-free high Tg and high CTI flame retardant resin composition according to claim 5, characterized in that: In step three, the mass ratio of the total mass of the eugenol-based cyclotriphosphazene epoxy resin monomer, the glycidyl ether-type tetrafunctional epoxy resin and the hydrogenated styrene-butadiene-styrene block copolymer to the bisphenol A-type epoxy resin is 1:

1.

7. A halogen-free, high Tg, high CTI flame retardant resin composition prepared by the preparation method according to claim 6.

8. Use of the halogen-free, high Tg, high CTI flame retardant resin composition according to claim 7 in preparing a laminate.

9. A laminated board, characterized in that: The preparation method of the halogen-free high Tg and high CTI flame retardant resin composition according to claim 7 comprises the following steps: (1) Impregnation: impregnating the glass fiber cloth into a halogen-free, high Tg, high CTI flame retardant resin composition, and then drying it to obtain a prepreg; (2) Lamination: Use copper foil + 5 prepreg sheets + copper foil, and laminate neatly; (3) Pressing: hot pressing and curing to obtain a laminate substrate, the hot pressing and curing parameters are: The gelation temperature is 122-131°C, the pressure is 28-30 MPa, and the time is 1-1.2 hours; Curing temperature 158~163℃, pressure 48~51Mpa, time 1~1.1h; Post-curing temperature is 178-184°C, pressure is 30-33Mpa, and time is 0.8-1h.

10. The laminate according to claim 9, characterized in that The method also includes step (4) cutting: cutting off the edge material of the laminate substrate to obtain the laminate, and then packing after inspection.

Citation Information

Patent Citations

  • A halogen-free, medium-Tg, high-CTI flame-retardant epoxy fiberglass cloth base plate and its preparation method

    CN110561855B